Konstruksi Filosofi Manajemen Keuangan Institusi Pendidikan Kristen di Era Digitalisasi - Kuhu, Ryan Reflando; Pane, Exson; Hutagalung, Stimson (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2022)
Financial information systems in education institutions experienced transformation and progression. It moved from a conventional to a digital world that demands significant adaptation. Specifically speaking, Christian schools are far from academic exercises concerning financial information systems that are based on digital knowledge. This essay attempts to formulate the philosophy of financial information systems in Christian education institutions. By using the qualitative-descriptive method, this article invites articles, books, and other related sources that could contribute knowledge to the account. In sum, openness, expediency, and religious dimension are offered as an alternative philosophy to construct financial information system in a Christian school. AbstrakSistem informasi keuangan di institusi pendidikan mengalami perubahan dan progres. Bergerak dari model konvensional ke digital menuntut adaptasi yang siknifikan. Secara khusus, sekolah-sekolah Kristen jauh dari pengalaman akademik sehubungan dengan sistem informasi keuangan yang berdasarkan wawasan digital. Penelitian ini mencoba untuk mengformulasikan filosofi sistem informasi keuangan di institusi sekolah Kristen. Dengan menggunakan metode kualitatif-deskriptif, penelitian ini memanfaatkan artikel-artikel, buku-buku, serta referensi ilmiah lainnya yang dapat berkontribusi secara pengetahuan. Pada kesimpulannya, prinsip keterbukaan, kemanfaatan dan nilai keagamaan merupakan nilai filosofi alternatif yang ditawarkan bagi pengembangan sistem informasi keuangan di sekolah Kristen.